Lung Cancer Navigation and Care (Springer Nature, 2025)
This Open Access Lung Cancer Navigation and Care is the first site-specific, comprehensive clinical guide designed specifically for Lung Cancer Navigators and Allied Health Professionals. This essential resource delivers end-to-end foundational knowledge, clinical guidelines, best practices, and critical tools to elevate the standard of care and promote equitable health outcomes for individuals at risk for or living with lung cancer. With lung cancer remaining the leading cause of cancer-related deaths in the U.S. and globally, this guide addresses the urgent need for timely, evidence-based, and person-centered care. Each chapter is authored by multidisciplinary experts and seasoned navigators, offering in-depth content paired with real-world vignettes that illustrate practical application in patient navigation. Key takeaways, curated readings, and actionable resources conclude every chapter, making this a hands-on companion for clinical and community-based professionals alike. This textbook also confronts the disproportionate impact of lung cancer on historically marginalized communities and emphasizes the role of navigation in addressing social determinants of health. It highlights the promise of early lung cancer detection and innovations such as biomarker testing and targeted therapies, while advocating for the integration of nurses, community health workers, and allied health professionals across the care continuum. Whether used in clinical practice, professional development, or academic programs, Lung Cancer Navigation and Care is a groundbreaking resource that equips healthcare professionals to lead with knowledge, compassion, and impact.